Pengaruh Media Sosial Facebook Humas Pemerintah Terhadap Citra Positif Desa Sungai Sirihi Kecamatan Singingi (STMIK Dharmapala Riau, 2023)
This study aims to determine the influence of the government's social media Facebook Public Relations on the positive image of Sungai Sirih Village, Singingi District. As a social media owned by government institutions, of course, it is necessary to use good social media between the parties who determine the achievement of a positive image for Sungai Sirih Village, Singingi District. The research method used in this research is quantitative research. Quantitative research method is one type of research whose specifications are systematic, well- planned and clearly structured from the beginning to the making of the research design. In this study, the author uses the SPSS for Windows Version 20 computerized system to find out the influence of the government's social media Facebook Public Relations on the positive image of Sungai Sirih Village, Singingi District. From the test results, it is known that there is a significant influence of government Public Relations Facebook social media on the positive image of Sungai Sirih Village, Singingi District, so that the better the use of government Public Relations Facebook social media, the positive image of Sungai Sirih Village, Singingi District. Therefore, the use of good and effective government PR Facebook social media is very necessary, so that with the better use of government Public Relations Facebook social media, the positive image of Sungai Sirih Village, Singingi District, is also increasing.